Filosofia como a arte do bem viver : uma perspectiva aristotélica - Pormann, Bruna Nery (2017)
Philosophy as a way of life is the main content of the philosophical schools of antiquity; therefore, anyone who lived according to philosophical precepts was as a philosopher as the ones who possessed a more theoretical background. Philosophy in classical antiquity was not only a theoretical construction, but also a method of training people to live and perceive the world under a new paradigm. This is Pierre Hadot’s central idea, a philosopher who studied and defended philosophy as a way of life. The central idea of this study follows Hadot’s thesis: the eudaimonist ethics of Aristotle, a philosopher who has a great and consistent ethical treatise. The philosopher proposes an ethics based on actions, since, according to him, the will is not enough to change in fact. One must act for the facts to happen and, likewise, one must educate the desire for it to be allocated within the scope of the middle ground. In this sense, action becomes the path between reason and desire. However, there are two worlds: one where the desire was not educated and one where it already listens to and obey the reason. Thereby, when the desire has already been educated, one becomes a virtuous man, once one will always desire what is right. Thus, the desire begins to be felt only by what is appropriate, at the right time and in the right way. We may desire something that presents itself as something pleasurable, but it is not the field of the rational to desire the pleasure itself. In this way, pleasure is determinant, since it is necessary, but it does not occupy a sufficient place for it to be the motive or the realization of happiness. That is, one should not desire pleasure, but rather, if one wishes in the right way, it will already be pleasurable. Thus, the desire, once educated, begins to contribute to the good life and, consequently, leads us to eudaimonia, the good life. As a conclusion, the present study makes a theoretical essay, in which it shows approximations and distances between the ancient philosophers therapeutics the therapies existing in the contemporary scenario.